Prevalence of axial spondyloarthritis in patients with acute anterior uveitis: a cross-sectional study utilising MRI. Issue 1 (24th February 2018) - Sykes, Mark P; Hamilton, Louise; Jones, Colin; Gaffney, Karl
Abstract : Objective: Acute anterior uveitis (AAU) is the most common extra-articular manifestation of axial spondyloarthritis (axSpA). In this study, patients presenting with AAU were evaluated clinically and with MRI in order to estimate the prevalence of axSpA. Methods: Consecutive patients presenting to a university teaching hospital between February 2014 and March 2015 with AAU were invited to participate. Those with a history of chronic back pain (CBP) beginning <45 years were evaluated clinically and with MRI of thoracolumbar spine and sacroiliac joints. Results: Of 366 patients with AAU, 57 had a pre-existing diagnosis of axSpA; 77 others fulfilled the study eligibility criteria and 73 (95%) completed the study. Seventeen patients (23.3%) were diagnosed with axSpA by an experienced rheumatologist; of these, eight were human leucocyte antigen-B27 negative. Including those with a previous diagnosis, this equates to a minimum axSpA prevalence of 20.2%; one-quarter of patients were previously undiagnosed. Conclusion: This is the first study to actively search for the presence of axSpA in unselected patients presenting with AAU utilising MRI as an essential part of the assessment. There is a significant burden of undiagnosed axSpA in patients with AAU, but there does not appear to be a simple mechanism for screening. We recommend that ophthalmologists refer all patients with AAU with CBP, onset <45 years, to rheumatology for further evaluation.